Side effects of mesotherapy - review - Szwed, Weronika; Nowak, Alicja; Bogusz, Klaudia; Baran, Natalia; Maksymowicz, Marcela; Bielak, Adriana; Nowak, Aleksandra; Cywka, Łucja; Machowiec, Piotr; Ciecierski-Koźlarek, Hubert (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Microneedle mesotherapy is a non-surgical method consisting in controlled micropuncture of the skin with very thin needles, associated with the insertion of active substances into it. It is used in many fields of medicine, diseases, as well as cosmetic defects associated with the symptoms of skin aging. The aim of this review is to summarize the side effects described in the literature that may associated microneedle mesotherapy. The review was based on the available data collected in the PubMed database searched using the keywords "mesotherapy", "adverse effects", "side effects". Description of the state of knowledge: Complications of mesotherapy can be divided into infectious and non-infectious as well as local and systemic. The most common and best known are bruises and swelling caused by local inflammation caused by certain substances. More serious complications include anaphylaxis, skin necrosis, granulomas, cellulitis, and infectious complications. Summary: Mesotherapy is a commonly performed procedure not only by doctors, but also by non-medical people. Both patients and operators tend to underestimate the potential side effects of this method. We hope that raising awareness and paying attention to the errors made will contribute to reducing the complications associated with this procedure, as well as to its standardization.